The social representations of no-consensual pornografy (Research, Society and Development, 2022)
This research aimed to reveal the social representations in scenarios linked to the reproduction of pornography, interpret the sexual scripts that contribute to the occurrence of non-consensual propagation and understand the situations of vulnerabilities emerging in revenge scenarios. The method used was associated with the Theory of Social Representations in a socio-psychological approach. Data collection involved 34 young people between 18 and 29 years of age in a social network, in which we inserted a digital instrument, whose result was interpreted by the Content Analysis method, of the categorical analysis type, which generated eight themes: sexual scripts in Remote Control; the intimate as the place of sexuality and the exceptions to the rule; approximations and distances between pornography and eroticism; revenge as a state of vulnerability to the overlapping of the other; social vulnerabilities arising from non-consensual exposure; the interpersonal scripts of novels in vulnerable situations; political, programmatic, services and actions and social vulnerabilities; laughter and the discovery of the stranger through non-consensual pornography. We conclude that the social representation of the person implies relational games, whose concept remains between being subject and being object. The non-consensual bases for decision-making are prone to the production of pornography in the breakup of relationships, representing that the body can be consumed, but not identified and becomes an object for consumption when privacy runs out in front of the other's gaze.